Intermittent Oral Versus Intravenous Alfacalcidol in Dialysis Patients - Mitwalli Ahmed (Saudi Journal of Kidney Diseases and Transplantation, 2000)
Patients with end-stage renal failure (ESRF) on maintenance dialysis, commonly develop secondary hyperparathyroidism and renal osteodystrophy (ROD). Alfacalcidol, taken orally or administered intravenously, is known to reverse these complications. In this study, 19 ESRF patients, who were on dialysis (13 on hemodialysis and six on peritoneal dialysis) for longer than six months and having serum parathormone levels at least four times normal and serum calcium less than 2.1 mmol/L, were randomly allocated to treatment with oral or intravenous (i.v.) alfacalcidol for a period of 12 months. There were six patients on hemodialysis (HD) and three on peritoneal dialysis (PD) in the oral treatment group while in the i.v. group there were seven patients on HD and three on PD. Clinical and serial biochemical assessments showed no statistically significant difference between the orally- and i.v.-treated patients in terms of suppressing secondary hyperparathyroidism and osteodystrophy. However, patients with features of mild ROD on bone histology, had more satisfactory changes in biochemistry when compared to others. Our results further support the use of intermittent oral alfacalcidol in ESRF patients because of its cost effectiveness, ease of administration and convenience, especially for peritoneal dialysis patients.